Replacing two conserved amino acids, (Asn-52 to Val and Try-67 to phe), in the Iso-1-cytochrome c gene has little effect on the function of the protein. - McOdimba, F.A. (Concordia University, 1994)
Tyr-67 and Asn-52 are among the conserved residues in the amino acid sequence of eukaryotic cytochromes c. These residues, together with Thr-78 are hydrogen bonded to a buried water molecule, (Wat-l66), which is also a conserved structural feature in all naturally occuring eukaryotic cytochromes c whose three dimensional structures have been determined. . Previous studies have suggested that during oxidation-reduction states W at- 166 plays a role in shifting both the side chains and the main chain at the bottom of the protein molecule. Replacement of Tyr-67 in rat cytochrome c with Phe and Asn-52 with He in yeast cytochrome c have been shown to result in more thermally stable proteins than the wild type. The Asn-52 to He mutation also results in exclusion of W at -166 with a substantial re-organization of hydrogen bonding in that region. Other replacement at position 52 using Ala for Asn result in a functional protein. The objective of this project was to replace the two conserved amino acids around the heme environment in the yeast iso-I-cytochrome c with a view of destabilizing Vat-166. The two amino acids (Tyr-67 and Asn-52) were replaced with Phe and Val on the wild type iso-I-cytochrome c gene in a multi-copy pING4 expression plasmid vector which already had a Cys-l 02 to Thr mutation. Yeast cells carrying the triple mutant cytochrome c gene were iv propagated on media with glycerol as the source of carbon. These mutant cells had similar growth pateros as those carrying the wild type gene in the absence of glucose, suggesting that the extra mutations did not have any effect on the expression of a functional cytochrome c in yeast. Cytochromes c were extracted and purified from yeast cells carrying the mutant and wild type genes. The total protein yields were comparable in both cases. The specllum of the oxidized form of the purified mutant protein showed a shift in the 69Snm peak to 70Snm, indicating that the intergrity of the methionine sulfur bonding with the heme. Kinetic assays using polarographic method with purified beef heart cytochrome oxidase showed similarities between the wild type and mutant proteins in the characteristic two activity sites on the oxidase with similar V max l & V m',,2 and Kml around the micro molar range and Km2 around the nano molar range for both proteins, suggesting that the mutations did not affect the conformational structure of the cytochrome c molecule.